2012
DOI: 10.1371/journal.pone.0033871
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Bioenergetic Alterations in Mouse Neuroblastoma Cells Infected with Sindbis Virus: Implications to Viral Replication and Neuronal Death

Abstract: The metabolic resources crucial for viral replication are provided by the host. Details of the mechanisms by which viruses interact with host metabolism, altering and recruiting high free-energy molecules for their own replication, remain unknown. Sindbis virus, the prototype of and most widespread alphavirus, causes outbreaks of arthritis in humans and serves as a model for the study of the pathogenesis of neurological diseases induced by alphaviruses in mice. In this work, respirometric analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 65 publications
3
40
1
Order By: Relevance
“…Also, for hepatitis C virus (HCV)-infected cells, massive generation of ROS and a decreased ⌬ m were described (2). Mitochondrial dysfunction and ROS generation were observed 24 h after infection of a mouse neuroblastoma cell line by Sindbis virus, the prototype member of the alphavirus genus within the family Togaviridae (26). In contrast to these observations, we found that the metabolic activities of mitochondria are maintained through the entire RV replication cycle.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Also, for hepatitis C virus (HCV)-infected cells, massive generation of ROS and a decreased ⌬ m were described (2). Mitochondrial dysfunction and ROS generation were observed 24 h after infection of a mouse neuroblastoma cell line by Sindbis virus, the prototype member of the alphavirus genus within the family Togaviridae (26). In contrast to these observations, we found that the metabolic activities of mitochondria are maintained through the entire RV replication cycle.…”
Section: Discussioncontrasting
confidence: 86%
“…HCV-infected cells show an impairment of OXPHOS, which appears to be mainly due to a reduction in the activity of RC complex I of up to 50% (30). The respiratory capacities of complexes I and II decrease when Sindbis virus infection of a mouse neuroblastoma cell line proceeds (26). An increase in the activities of both the respiratory complex IV and the ATP synthase has been described to occur after HIV-1 infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in macromolecular synthesis for the generation of viral components also trigger synthesis of host factors that promote cell sustenance and survival resulting in an overall increase in the host cell biosynthetic activity [22]. Earlier studies in Sindbis virus infection, the prototype Alphavirus, have identified modulation of mitochondrial bioenergetics to favor ATP synthesis that is required to support active viral replication [23]. Similarly, in our study we see that the mitochondrial proteins are regulated during CHIKV infection in the HEK293 cell line.…”
Section: Changes In Cellular Energy Metabolismsupporting
confidence: 76%
“…As infection progresses, cellular stress increases, however, host cells have developed strategies to compensate metabolic shift as an attempt to maintain energy homeostasis and cell viability. Mitochondrial bioenergetics’ and metabolic balance are among the fundamental mechanisms used by cells to become tolerant to the stress caused by viral [10] or bacterial [11] infection. However, the extent to which parasites such as N. caninum alter host cell metabolism for their own replication, and the consequence of this disruption, remain unknown.…”
Section: Introductionmentioning
confidence: 99%